Implementation of the Sport Pedagogy Model to Improve Students’ Spatial Intelligence in Volleyball: Bibliometric Study 2020-2025 - Ifan Badra Wijaya; Hafit Amilin; Gita Ariesta; Nandika Juniano; Elizabeth Devi Rahmawati; Siti Baitul Mukarromah; Adi S (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the development of publication trends and identify and examine the main factors influencing the implementation of the sports pedagogy model to improve students’ spatial intelligence in volleyball learning. Methodology: This study uses bibliometric analysis and a Systematic Literature Review (PRISMA) based on Scopus data from 2020-2025 on sports pedagogy for developing students’ spatial intelligence in volleyball learning. The data obtained were then systematically selected, subjected to VOSviewer-based visualization analysis, and interpreted to identify patterns, relationships, and research trends related to the comprehensive and objective development of students’ spatial intelligence. Main Findings: Research results show that implementing sports pedagogy in volleyball instruction improves students' spatial intelligence through game-based cognitive and motor integration. The growing body of research indicates the high relevance of learning implementation, which is influenced by engagement, tactical skills, decision-making, and the roles of teachers and learning design. However, this research remains limited by data sources, design variations, country dominance, and a lack of longitudinal studies, necessitating innovative development, expanded research, and technology integration. Novelty/Originality of this study: This study offers a comprehensive bibliometric perspective by integrating trend analysis, spatial intelligence, and sport pedagogy in the context of volleyball learning. It enriches existing research by emphasizing the relationship between cognitive and motor aspects and providing a conceptual basis for the development of innovative learning models.